2018
DOI: 10.3389/fendo.2018.00505
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Unmet Needs in the Therapeutics of Bone Fragility

Abstract: The prevalence of fragility fractures increases as longevity increases the proportion of the elderly in the community. Until recently, the majority of studies have targeted women with osteoporosis defined as a bone mineral density (BMD) T score of < −2.5 SD, despite evidence that the population burden of fractures arises from women with osteopenia. Antiresorptive agents reduce vertebral and hip fracture risk by ~50 percent during 3 years but efficacy against non-vertebral fractures, 80% of all fractures in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 101 publications
(123 reference statements)
0
14
0
Order By: Relevance
“…Studies have shown that osteoanabolic agents stimulate bone formation and reduce fracture risk in patients with low bone density (1820). Since an adverse side effect of irradiation is decreased bone density and increased bone fragility, combination therapies of osteoanabolic, or anti-resorptive agents may be useful for patients receiving irradiation therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that osteoanabolic agents stimulate bone formation and reduce fracture risk in patients with low bone density (1820). Since an adverse side effect of irradiation is decreased bone density and increased bone fragility, combination therapies of osteoanabolic, or anti-resorptive agents may be useful for patients receiving irradiation therapies.…”
Section: Introductionmentioning
confidence: 99%
“…29 Furthermore, although findings about fracture prevention are encouraging, the assertion that abaloparatide is more effective than teriparatide in reducing fracture risk seems somewhat questionable. In fact, a large number of patients reporting a fragility fracture in the placebo and teriparatide groups sustained the traumatic event during the first few weeks of treatment 28,30 and the differences in fracture rates between the two treatment arms were minimal at 12 and 18 months. 9,30,31 Moreover, the observations of both enhanced anabolic effect and lower bone resorption with abaloparatide use compared to teriparatide therapy have also been questioned.…”
Section: New Anabolic Drugs: Abaloparatidementioning
confidence: 99%
“…It is to emphasize that remodelling imbalance occurring around the ages of 45-50 years, produce irreversible deficits in bone volume, microstructural deterioration and bone fragility. Starting an anti-resorptive therapy in late postmenopause doesn't reverse existing microstructural deterioration and doesn't abolish bone fragility [215]. Despite the concern emerging from the large, long-term RCT Women's Health Initiative (WHI) study about the safety of hormonal replacement treatment, post hoc subgroup analyses, stratifying women according to their age and time since menopause, have allowed to better understand the relationship between MHT and cardio-vascular risk.…”
Section: Sex Disparity In Osteoporosis Risk and Preventionmentioning
confidence: 99%